(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
Estimation of age of bloodstain found at scene of crime is crucial for forensic personnel, which aids in defining time frame in which the individual depositing it was present. Although many methods have been discovered to estimate age of the bloodstain but only few have gained widespread use due to poor time resolution and weak age correlation. The present study used UV–vis spectrophotometric analysis of hemoglobin (Hb) for estimating the age of the bloodstains spotted on different substrates, which are usually encountered at crime scene. The average rate of Hbsoret Band blue-shift rate varied from 0.0075 to 0.0015 nm/h for bloodstain of environmental exposure while for room temperature exposed it varied from 0.0012 to 0.0002 nm/h. Preliminary blood test (benzidine test), serological test (species of origin) and genetic analysis (DNA extraction) on the same bloodstain were also performed. The benzidine test and octerlony double diffusion test was positive for the samples kept at RT for 73 day while DNA could not be extracted.